(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2012)
Bangladesh is a developing country and has a lot of factories for different products for local use and also export to abroad. Garments industries are one of the top most items of exported items. A huge number of populations are working in garments industries. But these factories are not well designed in sense of the thermal environment. Workers experiences sickness related to indoor environment. The productions of these factories are affected due to employees’ health condition. The research is done in two different methods. One is empirical data collection using thermal data loggers and the other is questionnaire survey on the spots for three factory buildings. The field study was conducted in four different months of the same year during winter and summer period. Expected findings of this research are that the indoor environment is not comfortable for works at day time during summer season. This research will help the factory workers in providing a comfortable thermal environment and also help the employers or factory owners to increase their production margin.